Efektivitas Ekstrak Daun Mimba (Azadirachta indica A. Juss) terhadap Hama Ulat Grayak, Spodoptera frugiperda J.E. Smith Pada Tanaman Jagung (JURNAL ENFIT : Entomologi dan Fitopatologi, 2023)
Corn (Zea mays L.) is a multifunctional plant that has many use and all parts of the plant can be used for various purposes, therefore corn has an important meaning in industrial development in Indonesia because it is a raw material for the food industry. The tests were arranged using a Completely Randomized Design (CRD), which consisted of 5 treatments and 4 replications and 1 control as a comparison. A0 : control (water), A1 : extract with 20% concentration, A2 : extract with 40% concentration, A3 : extract with 60% concentration, A4 : extract with 80% concentration. Based on the results of the study of neem leaf extract on larvae S. frugiperda immersing bythe feed, then observations were made to see the behavior that appeared after the larvae ate the feed such as become less active, decrease appetite and avoid feed. Based on the observation of the mortality rate oflarvae S. frugiperda which were applied using neem (leaf extract,A. indica)there were differences in the percentage of mortality in each treatment. Based on the results, the percentage of mortality at 13 days showed that the treatment with the highest concentrations of A4 and A3 was 98-100%, while in the A1 treatment it only reached 53% and in the A2 treatment the mortality was only 63%. Based on the results of the study, it can be concluded that neem leaf extract (A. indica) has an effect on the mortality oflarvae S. frugiperda. At 10 dsa a concentration of 40% (A2) neem leaf extract was effective in causing 53% mortality. After carrying out this research, it can be suggested to also test the control of S. frugiperda larvae using neem (A. indica) leaf extract on the field.